2023
DOI: 10.7554/elife.80428
|View full text |Cite
|
Sign up to set email alerts
|

Antibody levels following vaccination against SARS-CoV-2: associations with post-vaccination infection and risk factors in two UK longitudinal studies

Abstract: Background: SARS-CoV-2 antibody levels can be used to assess humoral immune responses following SARS-CoV-2 infection or vaccination, and may predict risk of future infection. Higher levels of SARS-CoV-2 anti-Spike antibodies are known to be associated with increased protection against future SARS-CoV-2 infection. However, variation in antibody levels and risk factors for lower antibody levels following each round of SARS-CoV-2 vaccination have not been explored across a wide range of socio-demographic, SARS-Co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
3
11
0
Order By: Relevance
“…Our findings are consistent with previous immunology studies that reported higher antibody levels following BNT–BNT versus AZ–AZ, 17 , 18 , 19 including studies in dialysis and kidney transplant recipients. 6 , 20 Higher effectiveness for BNT–BNT versus AZ–AZ has also been reported during the Delta wave in study populations not restricted to individuals with kidney disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with previous immunology studies that reported higher antibody levels following BNT–BNT versus AZ–AZ, 17 , 18 , 19 including studies in dialysis and kidney transplant recipients. 6 , 20 Higher effectiveness for BNT–BNT versus AZ–AZ has also been reported during the Delta wave in study populations not restricted to individuals with kidney disease.…”
Section: Discussionsupporting
confidence: 93%
“…The administration of BNT as a third dose appeared to compensate for the discrepancies in protection between AZ- and BNT-primed individuals. This finding is consistent with observational and clinical studies of third-dose immunogenicity in healthy adults 17 , 25 and individuals with kidney disease, 7 , 9 , 26 as well as vaccine effectiveness data from the general population. 27 One previous study explored short-term vaccine effectiveness of BNT as a third dose following AZ or BNT priming among haemodialysis recipients, reporting increased protection against Omicron infection for boosted compared with unboosted individuals and no significant differences according to primary vaccine group.…”
Section: Discussionsupporting
confidence: 89%
“…The trimeric S protein is a prominent immunological component of the virion surface and plays a crucial role in SARS-CoV-2 binding and entry to the host cell, mediating the interaction of the virus with the cellular receptor angiotensin-converting enzyme 2 (ACE2) and the subsequent fusion of the virus envelope with the host cell membrane. It has been clearly established that the production of S-specific antibodies that can neutralize the virus is crucial to confer protection against SARS-CoV-2 infection [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations consider vaccine-induced antibody titers as a marker of immune protection from infection or severe COVID-19 illness [ 11 , 12 , 13 ] but no antibody threshold at which to recommend booster dosing after the primary vaccine series has been determined [ 14 ]. Some studies report threshold antibody levels required for 50 or 70% protection against the ancestral and early SARS CoV-2 variant strains but note that the risk of infection changes gradually with the antibody titers [ 15 , 16 , 17 , 18 ]. The World Health Organization (WHO) has established standardized units for antibodies against SARS-CoV-2 (BAU/mL; binding assay); however, reported titers may be affected by the assays used, the vaccinated populations studied and the prevalent viral variant strains [ 16 ], making comparisons between studies difficult.…”
Section: Introductionmentioning
confidence: 99%